Urgensi Pembuatan Akta Kesaksian dan Akta Pernyataan Ahli Waris Oleh Notaris - Juristie Widyadhana; Putri Kemalasari; Shania Anindya Fitriani (Faculty of Law, University of Jember, Indonesia, 2024)
In matters of inheritance, an individual requires evidence to prove that they are legitimate heirs of the deceased.The Deed of Inheritance Testimony and The Deed of Heirs' Statement are deeds that are used as the basis for creating a Deed of Information on Inheritance Rights. In this research, we will discuss the urgency of creating a Deed of Inheritance Testimony and a Deed of Heirs' Statement and what consequences will occur to the Notary if they do not make these two deeds. The research method in this research is normative juridical, namely research using library materials or secondary data. This data will be analyzed qualitatively so that it will produce analytical descriptive data. Based on the research, it was found that the Deed of Inheritance Testimony and the Deed of Heirs' Statement have an important role in growing the Notary's confidence when creating a Deed of Information on Inheritance Rights and as security for the Notary himself because they can be used as evidence when there are problems related to heirs. As a result of not creating these two deeds, there are no sanctions given, but it can put the notary's position and position at risk of being exposed to problems from the Deed of Information on Inheritance Rights that has been made. KEYWORDS: Deed of Inheritance Testimony, Deed of Heirs' Statement, and Notary